2019
DOI: 10.1038/s41467-018-08025-9
|View full text |Cite|
|
Sign up to set email alerts
|

In-situ formation of one-dimensional coordination polymers in molecular junctions

Abstract: We demonstrate the bottom-up in-situ formation of organometallic oligomer chains at the single-molecule level. The chains are formed using the mechanically controllable break junction technique operated in a liquid environment, and consist of alternating isocyano-terminated benzene monomers coordinated to gold atoms. We show that the chaining process is critically determined by the surface density of molecules. In particular, we demonstrate that by reducing the local supply of molecules within the junction, ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 47 publications
6
46
1
Order By: Relevance
“…However, many compounds which have been measured as single-entity junctions in the literature might be capable of forming H-bonded chains, but evidence of in situ formation of oligomeric entities during a break-junction experiment is scarce. Examples of such oligomerisation processes available in the literature are limited to those involving coordination or chemical bonds, such as metallopolymers formed by abstraction of metal atoms from the two electrodes, 37 spontaneous dimerization of organotin compounds, 38 and, recently, fieldinduced catalytic oligomerisation of terminal anilines. 39 We believe the peculiar behaviour of imidazole can be attributed to its particularly high moment of dipole, measured at 3.67 D (as comparison, H 2 O = 1.83; HCN = 2.98; acetonitrile = 3.44).…”
Section: Discussionmentioning
confidence: 99%
“…However, many compounds which have been measured as single-entity junctions in the literature might be capable of forming H-bonded chains, but evidence of in situ formation of oligomeric entities during a break-junction experiment is scarce. Examples of such oligomerisation processes available in the literature are limited to those involving coordination or chemical bonds, such as metallopolymers formed by abstraction of metal atoms from the two electrodes, 37 spontaneous dimerization of organotin compounds, 38 and, recently, fieldinduced catalytic oligomerisation of terminal anilines. 39 We believe the peculiar behaviour of imidazole can be attributed to its particularly high moment of dipole, measured at 3.67 D (as comparison, H 2 O = 1.83; HCN = 2.98; acetonitrile = 3.44).…”
Section: Discussionmentioning
confidence: 99%
“…To date, a large range of such functionalities have been realized experimentally, with molecules being employed as transistors, 3,18,[29][30][31] diodes, [32][33][34][35][36][37][38][39] resonanttunneling diodes, 40 switches, 12,13,41,42 light-emitters, 43 photoresponsive devices, 44 memory elements, 45 thermoelectric power generators, 14,15,46 potentiometers 47 and strain-sensors. 26 Common approaches in the design of single-molecule devices are the engineering of the coupling to the electrodes via various anchoring groups, [48][49][50][51][52] and controlling the level alignment of the molecular orbitals closest to the Fermi energy of the contacts, either by chemical means 53 or using an electrostatic gate (solid-state 3,[18][19][20][21][29][30][31] or an electrochemical [54][55][56][57] ), and the exploitation of quantum effects such as destructive interference.…”
mentioning
confidence: 99%
“…Recent work has reported that additional conductance states may arise from in-backbone molecule-electrode linkages, 9,[18][19][20][21] in situ dimerization, 17,[22][23][24] or intermolecular interactions. [25][26][27] To investigate the origin of the high G state, we synthesized the non-C2-symmetric terphenyl derivative R6-H containing only one terminal anchor using automated iterative cross-coupling (Fig.…”
Section: Role Of Alkyl Side Chain Length On Molecular Charge Transportmentioning
confidence: 99%